2023
DOI: 10.1111/1755-0998.13806
|View full text |Cite
|
Sign up to set email alerts
|

Sequence capture: Obsolete or irreplaceable? A thorough validation across phylogenetic distances and its applicability to hybrids and allopolyploids

Abstract: The rapid development of sequencing technologies during the past decades has led to the onset of so-called third-generation sequencing (Schadt et al., 2011) and made sequencing easier and cheaper, enabling scientists to gather huge amounts of sequence data. Consequently, whole-genome sequencing (WGS) approaches are widely used nowadays (e.g. Rosenquist et al., 2022;Schwarze

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
2
1
0
Order By: Relevance
“…As expected, the success of target‐capture (assessed from on‐target mapping rates) decreased with increasing genetic distance from the reference species C. finmarchicus (Choquet et al., 2019), with C. hyperboreus (presumably the most genetically divergent species) having the lowest number of sequences captured, behind C. helgolandicus . This trend is typical of target‐capture‐based methods (Bartoš et al., 2023) and was also reported in Choo et al. (2020) using a similar protocol, with capture probes designed for the pteropod Limacina bulimoides and applied to congeneric species.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…As expected, the success of target‐capture (assessed from on‐target mapping rates) decreased with increasing genetic distance from the reference species C. finmarchicus (Choquet et al., 2019), with C. hyperboreus (presumably the most genetically divergent species) having the lowest number of sequences captured, behind C. helgolandicus . This trend is typical of target‐capture‐based methods (Bartoš et al., 2023) and was also reported in Choo et al. (2020) using a similar protocol, with capture probes designed for the pteropod Limacina bulimoides and applied to congeneric species.…”
Section: Discussionsupporting
confidence: 71%
“…As expected, the success of target-capture (assessed from on-target mapping rates) decreased with increasing genetic distance from the reference species C. finmarchicus (Choquet et al, 2019), with C. hyperboreus (presumably the most genetically divergent species) having the lowest number of sequences captured, behind C. helgolandicus. This trend is typical of target-capture-based methods (Bartoš et al, 2023) and was also reported in Choo et al (2020) using a similar protocol, with capture probes designed for the pteropod Limacina bulimoides and applied to congeneric species. We were able to yield 1535 high-quality SNPs across four Calanus species, and 6030 SNPs for the investigation focused TA B L E 4 Results from the investigation of the 10 microsatellite loci from which hybrids between Calanus finmarchicus and C. glacialis were detected.…”
Section: Scaling Up the Exploration Of Hybridization In Calanus Spp W...supporting
confidence: 64%
See 1 more Smart Citation